Detection of biomolecules using optoelectronic biosensor based on localized surface plasmon resonance. Nanoimprint lithography approach - Chegel, V.; Luca, B.; Guo, J.; Lopatynskyi, A.; Lopatynska, O.; Poperenko, L. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
In this work, we use a nanoimprint lithography fabrication technology to
create uniformly-oriented and homogenous noble metal nanoparticle arrays with wellcontrolled
size, shape and spacing, which can be the basis platform for the development
of Localized Surface Plasmon Resonance (LSPR) sensors for biomolecular detection.
Using this approach, we demonstrate proof-of-principle of an optical biosensor to
quantify biomolecular interactions in a real-time mode using a UV-visible
spectrophotometer. The sensor shows concentration-dependent kinetics of surface
adsorption or binding of biomolecules and a capability to monitor antigen-antibody
specific reactions, which is demonstrated by the reaction between bovine serum albumin
(BSA) and anti-BSA immunoglobulin.